2014
DOI: 10.1007/s10735-014-9606-z
|View full text |Cite
|
Sign up to set email alerts
|

Expression of HMGB1 in the periodontal tissue subjected to orthodontic force application by Waldo’s method in mice

Abstract: Recent studies indicate that high mobility group box protein 1 (HMGB1) originating from periodontal ligament (PDL) cells can be a potential regulator in the process of orthodontic tooth movement and periodontal tissue remodeling. The aim of this study is to investigate HMGB1 expression in periodontal tissue during orthodontic tooth movement in mice according to Waldo's method. Six 7-week-old C57BL6 mice were used in these experiments. The elastic band was inserted into the teeth space between the right first a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
10
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 34 publications
3
10
0
Order By: Relevance
“…In addition, by using a rat experimental tooth movement model, Wolf et al (2013c) showed HMGB1 expression was modulated in a time-dependent manner in both compression and tension sides. Our previous study also confirmed the orthodontic force-triggered up-regulation of HMGB1 in mice PDL (Lv et al 2014a). Considering the altered expression of periostin and HMGB1 in PDL cells under stress condition, it is possible that there is a correlation, direct or indirect, between both proteins, which may be involved in the modulation of stress-induced PDL remodeling.…”
Section: Introductionsupporting
confidence: 83%
See 1 more Smart Citation
“…In addition, by using a rat experimental tooth movement model, Wolf et al (2013c) showed HMGB1 expression was modulated in a time-dependent manner in both compression and tension sides. Our previous study also confirmed the orthodontic force-triggered up-regulation of HMGB1 in mice PDL (Lv et al 2014a). Considering the altered expression of periostin and HMGB1 in PDL cells under stress condition, it is possible that there is a correlation, direct or indirect, between both proteins, which may be involved in the modulation of stress-induced PDL remodeling.…”
Section: Introductionsupporting
confidence: 83%
“…Pn-/-mice were generated as described previously (Lv et al 2014a). In brief, the targeted disruption of the periostin gene was performed in mouse embryonic stem cells using a homologous recombination, and the inserted Neo gene was deleted in deficient mice by crossing with CAG-Gre mice to excise the neo cassette; no periostin expression was observed in Pn-/-mice.…”
Section: Animal and Tissue Preparationmentioning
confidence: 99%
“…Additionally, Li et al . confirmed an increase in HMGB1 translocation following exposure to mechanical cell stress within the periodontal ligament system. Interestingly, these researchers showed that HMGB1 upregulation is limited to cell‐rich periodontal ligament tissue and that no HMGB1 can be detected in cell‐free hyaline zones .…”
supporting
confidence: 54%
“… confirmed an increase in HMGB1 translocation following exposure to mechanical cell stress within the periodontal ligament system. Interestingly, these researchers showed that HMGB1 upregulation is limited to cell‐rich periodontal ligament tissue and that no HMGB1 can be detected in cell‐free hyaline zones . Based on these findings and the findings of other research groups, it can be hypothesized that as a result of expansion of hyaline zones, the overall expression of HMGB1 in the periodontal ligament can differ between studies and needs to be quantified in non‐hyaline tissue.…”
supporting
confidence: 54%
See 1 more Smart Citation